Impact of racial disparities and insurance status in patients with bone sarcomas in the USA: a population-based cohort study. Issue 5 (9th May 2022) - Hu, Xianglin; Fujiwara, Tomohiro; Houdek, Matthew T.; Chen, Lingxiao; Huang, Wending; Sun, Zhengwang; Sun, Yangbai; Yan, Wangjun
Abstract : Aims: Socioeconomic and racial disparities have been recognized as impacting the care of patients with cancer, however there are a lack of data examining the impact of these disparities on patients with bone sarcoma. The purpose of this study was to examine socioeconomic and racial disparities that impact the oncological outcomes of patients with bone sarcoma. Methods: We reviewed 4, 739 patients diagnosed with primary bone sarcomas from the Surveillance, Epidemiology and End Results (SEER) registry between 2007 and 2015. We examined the impact of race and insurance status associated with the presence of metastatic disease at diagnosis, treatment outcome, and overall survival (OS). Results: Patients with Medicaid (odds ratio (OR) 1.41; 95% confidence interval (CI) 1.15 to 1.72) and uninsured patients (OR 1.90; 95% CI 1.26 to 2.86) had higher risks of metastatic disease at diagnosis compared to patients with health insurance. Compared to White patients, Black (OR 0.63, 95% CI 0.47 to 0.85) and Asian/Pacific Islander (OR 0.65, 95% CI 0.46 to 0.91) were less likely to undergo surgery. In addition, Black patients were less likely to receive chemotherapy (OR 0.67, 95% CI 0.49 to 0.91) compared to White patients. In patients with chondrosarcoma, those with Medicaid had worse OS compared to patients with insurance (hazard ratio (HR) 1.65, 95% CI 1.06 to 2.56). Conclusion: In patients with a bone sarcoma, the cancer stage at diagnosis varied based on insurance status, and racial disparities were identified in treatment. Further studies are needed to identify modifiable factors which can mitigate socioeconomic and racial disparities found in patients with bone sarcomas. Cite this article: Bone Joint Res 2022;11(5):278–291.